A case report of a deep surgical site infection with Terrisporobacter glycolicus/T. Mayombei and review of the literature. Issue 1 (December 2016) - Cheng, Matthew; Domingo, Marc-Christian; Lévesque, Simon; Yansouni, Cedric
Abstract Background There are increasing data regardingTerrisporobacter glycolicus as an emerging anaerobic pathogen. However, the few published cases to date usually report it as part of a polymicrobial infection. Here, we describe the first reported monomicrobial surgical site infection with this bacterium. Identification methods, taxonomy, and clinical management of this rarely identified pathogen are also discussed. Case presentation A previously healthy 66-year-old sustained an open olecranon fracture of his left arm after trauma. He subsequently underwent open reduction and internal fixation (ORIF), with insertion of an olecranon locking plate and two locking screws. Ten days after surgery, the patient developed increasing pain at the surgical site and noted green discharge from the wound. Culture of the wound discharge yielded grew a pure Gram-positive anaerobe identified by the RapidANA® microbial identification system asC. difficile (profile 000010, 99.1 % probability). Reference laboratory testing identified the isolate asT. glycolicus/mayombei (previously designated as Clostridium glycolicum/mayombei) by 16S rRNA gene sequencing and asClostridium glycolicum by MALDI-TOF mass spectrometry. The patient received an 8-week course of moxifloxacin and metronidazole with an excellent clinical response at 12 months' follow-up. Conclusions We describe the case of a deep surgical site infection withT. glycolicus/mayombei (formerly known asClostridium glycolicum andClostridium mayombei, respectively), which extends our knowledge of the clinical spectrum ofthis pathogen . The isolate was misidentified by phenotypic identification methods.